(3TQM OjhGf GdTQja GdQVis - (3CHi Mcje YHO Gddg Hf EHQGgje Hf YHO Gddg GdNHQis; (3GdTQja GdQVj , CHh GdMSf eMeO Hf GdMSjf Hf ehSi GdQVj GdYdhj GdMSjfj GdehShj, CHh GdMSf,J (B406 (3g` s ((3jGbhJ GdeSJYUei s)
(3ChdgG (B:s
(3CQGc SJMOK ddbdH hLOG EPG GdQcGFH hOYf fLOG s
(3BNQgG (B:s
(3hQCi GdGJLGg dg aeVi jHZi GdfLGI ZOG s
(3GdTQja GdQVi hgh CHh GdMSf eMeO Hf ehSi GdeJhai (B406(3g`s
(3GdfSNI HgG MhGTs
(3eQJHkG Ydi GdCHhGH hGdbhGais
(3fSNI eYGQVI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs